A new name and a new combination for Syzygium (Myrtaceae) from tropical Africa - Byng, James W.; Snow, Neil (Phytotaxa, 2016)
A new name, Syzygium chimanimaniense, and a new combination, S. subcordatum, are provided for two poorly known montane African species. Diagnostic characters, distributions, specimens examined, and illustrations are provided for the two species for the first time. In addition, Syzygium micklethwaitii subsp. subcordatum var. dryas is synonymised with S. subcordatum, based on field and herbarium observations.